PRINCIPLES OF CONSTRUCTION OF THE NAVIGATION-LANDING SYSTEM FOR AIRCRAFT OF LOCAL AIRLINES - Kondrashov, Ya. V.; Fialkina, T. S.; Ryabets, A. P. (Science-based technologies, 2009)
The variants of construction and use of surface and side radio equipment are considered in the article, the indexes of quality of the system are certain, priorities are placed for its different modifications.